Pegasus : uma ferramenta de simulação para apoio ao design de jogos de progressão - Silva, Marcelo Arêas Rodrigues da. (2018)
The video game industry has shown great growth and the numbers show that it continues to expand. Simultaneously, the popularization of smartphones contributes to the growing inclusion of games in daily life. The process of building a game consists of a series of steps, the design being one of the initial stages. The game designer has the challenge of carrying the idea of his mind to the game in a satisfactory way. However, there are not many specialized tools to support this work. This thesis proposes an environment to support the design of games with progression structure, through a simulation tool. The proposal describes the interaction of the game designer with the simulator so that it can assist in the process of creating, testing and refining game elements before proceeding to the programming stage. To fulfill this purpose Pegasus progression game simulator was built, based on patterns for software development and patterns for game design. This thesis presents its architecture, operation and the experience using the tool to support the design of some games of different types. Finally, the conclusions and possibilities of tool expansion are exposed.